White blood, black gold : the commodification of wild rubber in the Bolivian Amazon, 1870–1920 - Córdoba, Lorena Isabel (2019)
Fil: Córdoba, Lorena Isabel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones; Argentina